Parental Involvement in the Selective Provision of Digital Access for Young Children - Saharudin Saharudin; Regita Riani Putri (Journal of Childhood Development, 2026)
This research explores parental involvement through the selective provision of children's access to digital technologies. Employing a qualitative exploratory case study design, data were generated through semi-structured interviews with six parents of kindergarten-aged children in a private school context. Interviews were carried out in Bahasa Indonesia, recorded, and transcribed word for word. Thematic analysis was utilized to examine the data for patterns in parental decision-making and regulation practices. The findings reveal three interconnected themes. First, parents enacted involvement through evaluative judgments of age appropriateness, focusing on children’s readiness and content suitability. Second, parents carefully determined the timing of children’s first digital exposure, often introducing devices gradually and intensifying access in response to schooling demands. Third, parental involvement was sustained through conditional access, where device use was regulated through supervision, time limitations, and purpose-driven rules. Overall, the study emphasizes that the digital access decision in early childhood is not a one-time thing, but rather a continual practice by the parents, influenced by the child's development and the specific circumstances. The study contributes to early childhood digital parenting literature by conceptualizing digital access as selective provision and offers policy implications for strengthening age-appropriate guidance and school–parent collaboration in managing children’s digital engagement. Furthermore, the novelty of this study lies in conceptualizing digital access not as mere availability, but as a socially mediated and developmentally negotiated practice of selective provision in early childhood. This study is novel in that it shifts the analytical focus from post-use regulation to pre-access decision-making, highlighting selective provision as a key dimension of parental mediation in early childhood.